Effect of source of nitrogen, organic manure and PSB application on groundnut (Arachis hypogaea L.) yield, P uptake in calcareous soil of southern Saurashtra: Effect of source of nitrogen, organic manure and PSB application on groundnut (Arachis hypogaea L.) yield, P uptake in calcareous soil of southern Saurashtra - KIRAN K REDDY; RAM A JAT; RAJA RAM CHOUDHARY (Journal of Oilseeds Research, 2020)
Twelve treatments consisting of two different nitrogen sources in combination with farm yard manure (FYM) and phosphate solubilizing bacteria (DGRC1) were used to quantify the effect on groundnut yield, enzymatic activities, P uptake and phosphorus use efficiency (PUE). Significantly high pod yield (2651 kg/ha) was obtained with the application of ammonium sulphate in addition to FYM and DGRC1. DGRC1 alone improved pod yield by over 200 kg/ha compared to control. Application of Urea+DGRC1 gave significantly higher pod yield (2444 kg/ha) than Ammonium sulphate + DGRC 1 (2216 kg/ha). Alkaline phosphatase activity, PUE, P uptake were significantly high with Ammonium sulphate+FYM+DGRC 1. Dehydrogenase activity was significantly high (5.8 µg TPF/g soil/h) when DGRC1 was applied alone. It was concluded that PSB (DGRC1) application enhances groundnut pod yield, improves PUE and other fertility parameters.